Simultaneous high-resolution detection of multiple transcripts combined with localization of proteins in whole-mount embryos - Gross-Thebing, Theresa (BioMed Central, 2014)
BACKGROUND: Whole-mount in situ hybridization (WISH) is a fundamental tool for studying the spatio-temporal expression pattern of RNA molecules in intact embryos and tissues. The available methodologies for detecting mRNAs in embryos rely on enzymatic activities and chemical reactions that generate diffusible products, which are not fixed to the detected RNA, thereby reducing the spatial resolution of the technique. In addition, current WISH techniques are time-consuming and are usually not combined with methods reporting the expression of protein molecules. RESULTS: The protocol we have developed and present here is based on the RNAscope technology that is currently employed on formalin-fixed, paraffin-embedded and frozen tissue sections for research and clinical applications. By using zebrafish embryos as an example, we provide a robust and rapid method that allows the simultaneous visualization of multiple transcripts, demonstrated here for three different RNA molecules. The optimized procedure allows the preservation of embryo integrity, while exhibiting excellent signal-to-noise ratios. Employing this method thus allows the determination of the spatial expression pattern and subcellular localization of multiple RNA molecules relative to each other at high resolution, in the three-dimensional context of the developing embryo or tissue under investigation. Lastly, we show that this method preserves the function of fluorescent proteins that are expressed in specific cells or cellular organelles and conserves antigenicity, allowing protein detection using antibodies. CONCLUSIONS: By fine-tuning the RNAscope technology, we have successfully redesigned the protocol to be compatible with whole-mount embryo samples. Using this robust method for zebrafish and extending it to other organisms would have a strong impact on research in developmental, molecular and cell biology. Of similar significance would be the adaptation of the method to whole-mount clinical samples. Such a protocol would contribute to biomedical research and clinical diagnostics by providing information regarding the three-dimensional expression pattern of clinical markers. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12915-014-0055-7) contains supplementary material, which is available to authorized users.